1972
DOI: 10.1002/ijc.2910100126
|View full text |Cite
|
Sign up to set email alerts
|

Detection of humoral antibody to the transmissible venereal tumour of the dog

Abstract: Humoral antibody against membrane-associutrd antigens of the transrnissiblc. venrrrul tiimoiir ( T V T ) of the dog was drmonstrated using the indirect membratir immiiriofluorescrnce test. Circulating antibody to the turnour, as well as in vivo coating of thc tumour cells with antibody, co~dd br detec-terl at 40 days or more after trunsplantution. Anti-TVT activity was contuined in the 19s. intermediate S and thiJ 7s.jrucfioiw of at1 crnti-T V T swum. No acritiry was iktrcted in the 3SSfractiori. A crossreucti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

1976
1976
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 11 publications
1
16
0
3
Order By: Relevance
“…Indirect and direct IF studies confirm and extend previous reports of the presence of circulating and cell-bound anti-CTVS antibodies in tumor-bearing dogs [II,19,20]. We noted also that tumor dog sera and even hyperimmune sera reacted only with a proportion of CTVS cells.…”
Section: Discussionsupporting
confidence: 78%
“…Indirect and direct IF studies confirm and extend previous reports of the presence of circulating and cell-bound anti-CTVS antibodies in tumor-bearing dogs [II,19,20]. We noted also that tumor dog sera and even hyperimmune sera reacted only with a proportion of CTVS cells.…”
Section: Discussionsupporting
confidence: 78%
“…Although CTVS cells have been shown previously to be coated with immunoglobulin during the progressive phase of tumour growth (Cohen, 1972;Bennett et al, 1975;Beschorner et al, 1979), the collagenase-dissociated and washed tumour cells used in this study were found to be free of immunoglobulin coating as assayed by immunofluorescence assay, indicating that the failure to demonstrate MHC antigens on progressively growing tumours was not due to masking of tumour cells with immunoglobulins.…”
Section: Discussionmentioning
confidence: 50%
“…Although there are significant differences between CTVT and DFT1, they share characteristics of transmissibility and MHC-I downregulation. Indeed the development of IgG antibodies against DFT1 cells may parallel what is believed to occur in CTVT cases: after the canine tumour has established there are increased numbers of MHC-I +ve CTVT cells discernible by immunohistochemistry and immunocytochemistry, and the development of serum IgG antibodies against CTVT cells occurs [8,9]. The experimentally induced CTVTs tend to regress [8], whereas the naturally occurring tumours seem to remain in equilibrium as locally invasive tumours with metastases being uncommon [14].…”
Section: Discussionmentioning
confidence: 99%